(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The form of estimating, analyzing and interpreting the mechanism and channels of influence that financial flexibility can have with its sub-indices represented by (Liquidity CU, Financial Leverage (FL), towards the value of the company (MVA) for a sample of companies listed on the Iraq Stock Exchange consisting of six companies and for the period (2012-2022).), the main goal that the research sought to achieve. To achieve this, in addition to proving its hypotheses, the research adopted the sum of pooled averages methodology based on the Autoregressive Distributed Lag and Pooled Mean Group (PMG/ARDL) methodology, based on data. The Balanced Longitudinal Panel Data, with a number of views amounting to (66) views, and its experimental results came to confirm that high levels of financial flexibility, whether through an increase in the liquidity index or through a decrease in the financial leverage index, are usually accompanied by positive effects on the company value index on... Long term due to the positive impact that financial flexibility has on the rise in the total market value of securities listed on the financial market, This calls for companies to pay attention to financial flexibility indicators and adopt them as a guide in their work because of their significant and effective role in controlling their sources of financing, protecting them from the risk of default, and supporting their ability to seize available investment opportunities, as well as confronting and overcoming financial crises by increasing the size of their assets compared to their debts and ensuring the availability of... Liquidity below the acceptable level.